Subtle Radiological Features of Splenic Avulsion following Abdominal Trauma. (9th November 2010) - Rehim, S. A.; Dagash, H.; Godbole, P. P.; Raghavan, A.; Murthi, G. V.
Abstract : Splenic trauma in children following blunt abdominal injury is usually treated by nonoperative management (NOM). Splenectomy following abdominal trauma is rare in children. NOM is successful as in the majority of instances the injury to the spleen is contained within its capsule or a localised haematoma. Rarely, the spleen may suffer from an avulsion injury that causes severe uncontrollable bleeding and necessitates an emergency laparotomy and splenectomy. We report two cases of children requiring splenectomy following severe blunt abdominal injury. In both instances emergency laparotomy was undertaken for uncontrollable bleeding despite resuscitation. The operating team was unaware of the precise source of bleeding preoperatively. Retrospective review of the computed tomography (CT) scans revealed subtle radiological features that indicate splenic avulsion. We wish to highlight these radiological features of splenic avulsion as they can help to focus management decisions regarding the need/timing for a laparotomy following blunt abdominal trauma in children.